Morphological Variation in Bumblebees (Bombus terrestris) (Hymenoptera: Apidae) After Three Decades of an Island Invasion. Issue 1 (28th February 2023) - Kardum Hjort, Cecilia; Smith, Henrik G; Allen, Andrew P; Dudaniec, Rachael Y
Abstract: Introduced social insects can be highly invasive outside of their native range. Around the world, the introduction and establishment of the eusocial bumblebee Bombus terrestris (L. 1758) (Hymenoptera: Apidae) has negatively impacted native pollinators and ecosystems. Understanding how morphological variation is linked to environmental variation across invasive ranges can indicate how rapidly species may be diverging or adapting across novel ranges and may assist with predicting future establishment and spread. Here we investigate whether B. terrestris shows morphological variation related to environmental variation across the island of Tasmania (Australia) where it was introduced three decades ago. We collected 169 workers from 16 sites across Tasmania and related relative abundance and morphology to landscape-wide climate, land use, and vegetation structure. We found weak morphological divergence related to environmental conditions across Tasmania. Body size of B. terrestris was positively associated with the percentage of urban land cover, a relationship largely driven by a single site, possibly reflecting high resource availability in urban areas. Proboscis length showed a significant negative relationship with the percentage of pasture. Wing loading and local abundance were not related to the environmental conditions within sites. Our results reflect the highly adaptable nature of B. terrestris and its ability to thrive in different environments, which may have facilitated the bumblebee's successful invasion across Tasmania. Graphical Abstract: